Prevalence and PCR based molecular characterization of goat pox virus from field outbreaks of Multan and Bahawalnagar, Pakistan - Ijaz, A; Jabeen, F; Ashraf, A; Naz, S (Journal of Bio-Science, 2019)
This study was designed to check the prevalence and PCR-based molecular characterization of goat pox virus (GTPV) in the Multan and Bahwalnagar regions of Punjab, Pakistan. Capripox virus (CPPV) is the cause of goat pox (GTP) and sheep pox (SPP) disease, it highly affects the morbidity and mortality rate of goats and sheep. In this study, the 80 tissues and blood samples of goats were collected on age basis from the goat farms, slaughter houses, tanneries and domestic animals. The epidemiological data was also collected. The collected samples were processed for DNA extraction. We characterized the goat pox virus (GTPV) with specific primers of P32 gene by PCR. Then each amplified product was analyzed by agarose gel electrophoresis visualized by UV fluorescence light. This study showed that Infants of goats (2-10 months) in Multan showed 25% while adult goat in Multan showed 14.2 % positive results. In Bahawlnagar, the affected infants of goats (2-10 months) found were 31.25% while adult infected goats were 11.1%. Both primers were equally effective for the characterization of unknown samples. The most effected goats were adult female and infants. J. bio-sci. 28: 95-103, 2020